British Government Policy in Managing Refugee Problems After the British Exit in 2020: A Review from International Law - Agistya Mahendra, Farhani; Wismaningsih; Maman Suherman, Ade (LPPM Universitas Harapan Bangsa, 2025)
The United Kingdom's withdrawal from the European Union on February 1, 2020, through Brexit (British Exit) has had significant implications for the country's refugee policies. Before Brexit, the UK's refugee policies were subject to the Dublin Convention established by the European Union, which regulated the distribution quota of refugees among member states. This provision was considered detrimental to the UK due to the surge in the number of refugees it was required to accommodate. Post-Brexit, the UK implemented a new policy, the New Plan for Immigration, which has been criticized for being inconsistent with the 1951 Convention On the Status of Refugees. This study analyses the international legal framework concerning refugee protection and evaluates the UK's policies in handling refugees after Brexit. The research employs a juridical approach using historical, statutory, and comparative methods. The secondary data is collected through literature studies and analyzed qualitatively and descriptively. The findings indicate that international refugee protection is governed by the 1951 Convention and its 1967 Protocol, the 1948 Universal Declaration of Human Rights, and other regional legal instruments. Post-Brexit, the UK faces uncertainty in handling asylum seekers as it is no longer bound by the Dublin Convention or the Eurodac system of the European Union. No formal agreement has been established between the UK and the EU regarding asylum management, creating challenges in the UK's immigration policies.